Lagi kitang mamahalin a tribute to a national artist - Toledo, Josefino Musical Director, Arranger and Conductor (Viva Records Corp., 2003)
In this scene from the Sarzuela Paglipas ng Dilim made famous by National Artist for Theater, Atang de la Rama, the rich and wordly Caridad, played by Rosel Nava tries to distract Ricardo who has fallen in love with the seamistress Estrella